Estudio de prefactibilidad para el diseño e instalación de una planta para la producción de sidra a partir de manzana delicia (Pyrus malus D) - Lescano Muñoz, Claudia Paola (2020)
The main objective of this project is to determine the technical, economic, financial and market viability, through a preliminary study for the design and installation of a cider factory from Delicia apple. In the chapter on Market Research, our target market was identified. As a result, our product would be accepted in sectors A and B of Lima Metropolitana, which represents 26.5% of the population. Likewise, as it is an alcoholic beverage, it will be sold only to people over 18 years of age, which is, 71% of the inhabitants. Thanks to the segmentation and the support of a survey of 477 people, a project demand of 535,941.54 bottles of cider of 330ml corresponding to the first year will be presented. Later, a macro and micro location study was carried out in order to obtain the most optimal location for the project. In that way, the cities of Lima, Ica and Ancash were first evaluated considering different factors, where Lima was chosen, mainly because of its proximity to the raw material. Finally, the plant will be located in Ate, as it is the industrial area closest to the market compared to the other alternatives evaluated. On the other hand, the size of the plant was established from the analysis of different factors, obtaining a size of 636,430.58 annual units defined by the size - market relationship. In addition, at least 434,764 units per year would have to be produced to make a profit. Regarding the engineering of the project, it was observed that the fermentation operation represents the bottleneck of the process, with a capacity of 815,823.82 bottles. In addition, the plant layout was established, determining a total area of 750 m2. Referring to the economic and financial evaluation, it was shown that the project is profitable, obtaining an economic VAN of S/.820,648.66, TIR of 35.68% and RP 2.89 years. In the same way, a financial VAN of S/.901,818.52, TIR of 46.07% and RP 2.43 years. The total investment requirement of the project is S/.1,280,614.82, which is financed the 30% at an annual effective rate of 11.55% and COK of 15.03%. Finally, as a social evaluation there is S/.67,400.78 of capital density, S/.0.71 of capital intensity and product-capital ratio of S/. 1.40.